IMPLEMENTASI MODEL GUIDED INQUIRY DENGAN VIDEO ANIMASI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - Diah Widianingsih; Yoga Fernando Rizqi; Amrina Izzatika; Riswanti Rini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Critical thinking is often an ability that can stimulate cognitive reasoning and is very important for students to have. However, in practice this ability is difficult to apply in science learning, in the application of this research is to determine the effect of the application of guided inquiry models based on animated videos on students' critical thinking skills. The method used is a quasi experiment method with a non-equivalent control group design. The sampling technique of this study used non-probability sampling technique with purposive sampling technique. The population of this study was 54 people and the samples used were students in class IV A and IV B. Data collection techniques with test. Hypothesis testing using simple linear regression with the results of Fhitung> Ftabel, namely 29.964> 4.26 and a significance value of 0.000 <0.05, so it can be concluded that there is a significant effect of applying the guided inquiry model based on animated video with IPAS material on the critical thinking skills of SD Negeri 1 Triharjo students.